Проблемы статусной легитимации политических и хозяйственных элит современного украинского общества - Черноволенко, В.; Иващенко, О.; Симончук, Е. (Социология: теория, методы, маркетинг, 1999)
The main focus of the article is a problem of elite groups status ligitimation, criteria which determinine public consciousness while choosing leaders, delegating them to power institutions and evaluating their activity. The research was aimed to define the power effectiveness estimation by population of Ukraine as a whole and Kiev habitants in particular.